Changes of the retinal thickness in the macula region in primary open-angle glaucoma patients measured with RTA analyzer - Polaczek-Krupa, Barbara; Grabska-Liberek, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: Aim of the study is to determinate retinal thickness in macula region in primary open-angle glaucoma patients and in patients suspected of primary open-angle glaucoma – by using retinal thickness analyzer RTA, as well as evaluation of the applicability of the method in the early diagnosis of primary open-angle glaucoma. Material and methods: Fifty primary open-angle glaucoma patient (95 eyes, average age 43.7 ± 9.0 years), and 67 patients suspected of primary open-angle glaucoma (128 eyes, average age 43.2 ± 11.0 years), underwent full ophthalmologic examination and also retinal thickness analysis with RTA analyzer. In particular, foveola average thickness VAV, foveal average thickness FAV, peri-foveal average thickness PFAV and posterior pole average thickness PPAV, were determined. The data were statistically evaluated and compared with those obtained for healthy subjects from the control group. Results: The retinal thickness values in the populations of primary open-angle glaucoma and primary open-angle glaucoma–suspected patients were: VAV 139.0 ± 20.5 µm i 147.6 ± 21.2 µm, FAV 149.9 ± 17.4 µm i 157.1 ± 18.6 µm, PFAV 173.0 ± 11.4 µm i 187.3 ± 15.6 µm oraz PPAV 168.1 ± 11.3 µm i 182.5 ± 14.8 µm, respectively. Statistically significant differences between both populations and the population of healthy subjects were observed. Conclusions: The retinal thickness in macula region in primary open-angle glaucoma and in patients suspected of primary openangle glaucoma was significantly lower than in the population of the healthy subjects. The method can be successfully applied in the early diagnosis of primary open angle glaucoma and be a valuable supplementary examination of the optic nerve disc and peripapillary area.